PSEUDOURIDINE AND N1-METHYLPSEUDOURIDINE IN mRNA VACCINES MODULATE RETINOIC ACID INDUCIBLE GENE I (RIG-I) AND TOLL-LIKE RECEPTORS (TLR) ACTIVATION - Ni Wayan Erly Sintya Dewi; Fatiha Khairunnisa; Nita Cahyawati; Muhammad Miftahussurur; Punta Indratomo (Jurusan Teknologi Laboratorium Medis, Poltekkes Kemenkes Denpasar, 2025)
Background: The advent of mRNA vaccines has underscored the significance of nucleoside modifications in regulating innate immune recognition. Pseudouridine (Î¨) and its derivative, N1-methylpseudouridine (m1Î¨), are widely used to enhance the efficacy and safety of mRNA vaccines.Objective: This review examines how Î¨ and m1Î¨ alter the activation of key innate immune sensors, including RIG-I, MDA5, and endosomal Toll-like receptors (TLR3, TLR7, TLR8).Methods: A narrative review was conducted using PubMed, Scopus, and Web of Science databases, focusing on studies evaluating the molecular and immunological effects of Î¨ and mÂ¹Î¨ on innate immune sensors.Discussion: Incorporation of Î¨ or m1Î¨ in mRNA markedly suppresses activation of TLR3, TLR7, and TLR8. Î¨-containing RNA avoids detection by TLR7/8 via two mechanisms: it resists endosomal nuclease digestion into immunostimulatory fragments and is poorly recognized by the TLR7/8 ligand-binding sites. m1Î¨ similarly evades nuclease processing yet, unlike Î¨, can directly activate TLR8. In the cytosol, Î¨/m1Î¨ modifications strongly reduce RIG-I signaling without impeding MDA5. Conclusions: By limiting innate PRR activation, these modifications increase the translation and stability of mRNA vaccines while reducing inflammatory interferon responses. This immune evasion is crucial for the high efficacy and tolerability of current mRNA vaccines; however, a trade-off exists between minimizing reactogenicity and the adjuvant benefits of innate stimulation.